Positron emission tomography tracers for synucleinopathies - Jie Xiang; Zhentao Zhang; Shengxi Wu; Keqiang Ye (Molecular Neurodegeneration)
Abstract Synucleinopathies, such as Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy, are characterized by the aggregation of α-synuclein. Variations in brain distribution allow for differentiation among these diseases and facilitate precise clinical diagnosis. However, distinguishing between synucleinopathies and Parkinsonism with tauopathies poses a challenge, significantly impacting clinical drug development. Therefore, molecular imaging is crucial for synucleinopathies, particularly for clinical diagnosis, assessment of drug efficacy, and disease surveillance. In recent years, advances in molecular imaging have led to rapid development of α-synuclein-specific tracers for positron emission tomography (PET), most of which are still in pre-clinical stages. Interestingly, some of these tracers share similar compound skeletal structures and are currently undergoing optimization for clinical application. Despite this progress, there remain challenges in developing α-synuclein tracers. This review summarizes recent findings on promising PET tracers and discusses representative compounds’ characteristics while offering suggestions for further research orientation.